ANALISIS VALUE CHAIN CUSTOM HADE SEBAGAI STRATEGI DIGITAL DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF - Faisal, Maulana Muhamad (LPPM Universitas Bina Bangsa, 2024)
This study examines the value chain analysis of Custom Hade and the role of Enterprise Resource Planning (ERP) and Customer Relationship Management (CRM) systems in enhancing operational efficiency and competitive advantage. Using a qualitative approach, this research explores how information technology integration can optimize business processes, reduce costs, and improve customer satisfaction. The findings indicate that the proper implementation of ERP and CRM can strengthen a company's competitiveness by improving supply chain coordination and customer service personalization